Attraction of Yellow Stem Borer (Scirpophaga incertulas Walker) to Different Colored Light-emitting Diodes - Yhone Arialistya; Suputa Suputa; Y. Andi Trisyono; Eka Firmansyah (Jurnal Perlindungan Tanaman Indonesia, 2019)
The yellow rice stem borer (Scirpophaga incertulas Walker) is a major pests on rice. Light traps have been used for monitoring and controlling S. incertulas with white and ultraviolet color light sources. The purpose of this research was to invent trap which uses an effective color that attracts S. incertulas. This research begins by sampling female S. incertulas pre-oviposition from the field then tested in the laboratory. The experiment was designed with factorial randomized block design with light colors and light intencity as factors. Light-emitting diodes used in this research, consisted of normal red, normal yellow, normal green, superbright red, superbright yellow, superbright green, superbright blue, UV, and white. LED white, UV, and superbright blue were attractive colors to S. incertulas  when exposure time was 15 minutes. Effective light intencity to attract S. incertulas was 1000 lux.